2016
DOI: 10.3892/mmr.2016.5981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miR-145 on the inhibition of chondrocyte proliferation and fibrosis by targeting TNFRSF11B in human osteoarthritis

Abstract: Osteoarthritis (OA) is a common cause of functional deterioration in older adults, and altered chondrogenesis is the most common pathophysiological process involved in the development of OA. MicroRNA‑145 (miR‑145) has been shown to regulate chondrocyte homeostasis. However, the function of miR‑145 in OA remains to be elucidated. In the present study, the expression levels of miR‑145 were examined in cartilage specimens from 25 patients with knee OA using reverse transcription‑quantitative polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Interestingly, miR-145 has recently been linked to fibrosis by overexpressing it in chondrocyte cell lines causing a significant inhibition of proliferation and fibrosis. The same observation was made when knocking down the assumed target tumor necrosis factor receptor superfamily, member 11b, in vitro [ 39 ]. In contrast, miR-145 -/- mice develop less severe lung fibrosis than wild-type mice in a pulmonary fibrosis model [ 40 ].…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, miR-145 has recently been linked to fibrosis by overexpressing it in chondrocyte cell lines causing a significant inhibition of proliferation and fibrosis. The same observation was made when knocking down the assumed target tumor necrosis factor receptor superfamily, member 11b, in vitro [ 39 ]. In contrast, miR-145 -/- mice develop less severe lung fibrosis than wild-type mice in a pulmonary fibrosis model [ 40 ].…”
Section: Discussionsupporting
confidence: 55%
“…Yet, others documented the downregulation of miR-145 in late stage OA AC, compared to early stage OA AC of the same patients [199] or normal AC [200]. Indeed, in human OA AC increased TNF-α levels correlated with a reduced miR-145 abundance [199].…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…Another miR-145 target in human AC cell lines is tumor necrosis factor receptor superfamily member 11b ( TNFRSF11B ). TNFRSF11B downregulation originates upregulation of Collagen II, V and X and reduction of MMP-1, MMP-8 and MMP-13 proteins [200]. Moreover, A disintegrin and metalloproteinase domain-containing protein 17 ( ADAM17 ) can be directly targeted by miR-145 [202], which initiates a negative feedback loop involving the ADAM17 substrate TNF-α, which is upregulated and subsequently reduces miR-145 expression in renal carcinoma cell lines [203].…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…MiR-145 is implicated in cartilage dysfunction in OA. A previous study reported that miR-145 regulates MKK4,14 SMAD3,13 Sox9,15 and TNFRSF11B16 expression by targeted binding in OA. However, whether miR-145 modulates ADAMTS5 expression by directly binding in OA tissues and cultured chondrocytes is unclear.…”
Section: Introductionmentioning
confidence: 95%